2003
DOI: 10.1007/s11661-003-0257-z
|View full text |Cite
|
Sign up to set email alerts
|

The low-cycle fatigue and fatigue-crack-growth behavior of HAYNES® HR-120 alloy

Abstract: The low-cycle fatigue and fatigue-crack-growth behavior of the HAYNES HR-120 alloy was investigated over the temperature range of 24°C to 980°C in laboratory air. The result showed that increasing the temperature usually led to a substantial decrease in the low-cycle fatigue life. The reduction of fatigue life could be attributed to oxidation and dynamic strain-aging (DSA) processes. The strain vs fatigue-life data obtained at different temperatures were analyzed. It was also found that the fatigue-crack-growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 57 publications
(46 reference statements)
1
4
0
1
Order By: Relevance
“…[20][21][22][23][24][25] The DSA can be considered to be due to the solute drag exerted on mobile dislocations by B and C atoms. Evidence of the solute drag during cyclic deformation in alloy 800H has been reported by Villagrana et al [20] An alternative mechanism of DSA has been proposed by Mulford and Kocks, [21] which was referred to as the dislocation-dislocation interaction model.…”
Section: B Serrated Flow Behavior and Dynamic Strain Agingmentioning
confidence: 99%
See 1 more Smart Citation
“…[20][21][22][23][24][25] The DSA can be considered to be due to the solute drag exerted on mobile dislocations by B and C atoms. Evidence of the solute drag during cyclic deformation in alloy 800H has been reported by Villagrana et al [20] An alternative mechanism of DSA has been proposed by Mulford and Kocks, [21] which was referred to as the dislocation-dislocation interaction model.…”
Section: B Serrated Flow Behavior and Dynamic Strain Agingmentioning
confidence: 99%
“…[21] The DSA increased the strain localization in the planar slip bands, and the impingement of these bands on grain boundaries, caused internal grain boundary cracks, and reduced fatigue life. [22,23,24] The mechanism of serrated deformation of IN718 alloy was studied by Chen and Chaturvedi. [25] They observed that the serrated flow in this alloy was due to the interaction of dislocations with precipitates.…”
Section: B Serrated Flow Behavior and Dynamic Strain Agingmentioning
confidence: 99%
“…13,14 Work on the low cycle fatigue of this alloy reports the occurrence of similar precipitates, although the research was carried out at lower temperatures. 15 Figures 8 and 9 show that the specimens treated for extended periods of time at 1120uC exhibit the highest tensile strength, which can be attributed to the high strain rate hardening that characterises single phase austenitic alloys. 16 Figure 10 shows that the material fulfils the resistance to fracture requirements at high temperature, but it shows the tendency to fracture towards shorter times in the specimen immersed in water as the that contribute in strengthening grain boundaries dissolve.…”
Section: Resultsmentioning
confidence: 98%
“…Crack length was measured by the crack-opening-displacement gauge using the unloadingcompliance method. [23,24] In a FCG test, data is recorded using a computer data-acquisition system and then plotted as crack length a vs the total number of elapsed cycles N. The crack growth rate da/dN is taken as the slope at some point of the curve, and it is a function of the stress level, crack size, and material properties. Mathematically, this crack propagation rate may be expressed in terms of the stress intensity factor, K [11] as follows:…”
Section: ½1mentioning
confidence: 99%